Assessing the role of minimally invasive radical hysterectomy for early-stage cervical cancer. (August 2022) - Bogani, Giorgio; Di Donato, Violante; Muzii, Ludovico; Casarin, Jvan; Ghezzi, Fabio; Malzoni, Mario; Greggi, Stefano; Landoni, Fabio; Bazzurini, Luca; Zanagnolo, Vanna; Multinu, Francesco; Angioli, Roberto; et al.
Highlights: Minimally invasive surgery for early-stage cervical cancer correlates with worse disease-free and cancer-specific survival. The surgical approach (minimally invasive vs open surgery) did not impact morbidity rates and quality of life. Minimally invasive radical hysterectomy (for stage IB disease) should be proposed only in the setting of clinical trials. Abstract: Surgery is the mainstay of treatment in the management of early-stage cervical cancer. Until the publication of the Laparoscopic Approach to Cervical Cancer (LACC) trial, minimally invasive radical hysterectomy was the recommended approach to treat patients with early-stage disease. The results of the LACC trial questioned the adoption of minimally invasive surgery in cervical cancer. In comparison with the open approach, minimally invasive surgery correlated with worse disease-free and cancer-specific survival. Similarly, other retrospective studies highlighted this correlation, thus corroborating the results of the LACC trials. In the present review, we evaluated current evidence and further prospective of the adoption of minimally invasive radical hysterectomy in cervical cancer. Moreover, we sought to assess some unsolved issues regarding the role of minimally invasive surgery in early-stage cervical cancer patients.